2013 IEEE Frontiers in Education Conference (FIE) 2013
DOI: 10.1109/fie.2013.6685007
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of cheating in online and traditional classes

Abstract: With classroom instruction undergoing a massive transformation to incorporate online learning techniques at unprecedented levels, technological advances have facilitated a range of mechanisms that improve teaching and learning. At the same time, these technological advances have also facilitated different forms of cheating in classes.Although the impact and implications of cheating have often been studied, we feel that this problem experiences constant evolution, and the dynamics of cheating, especially in onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…More specifically, the results on the group of cheating indicate that the most common acts are: Students look for answers in learning materials placed in locations that cameras cannot monitor; Students send test answers to each other through an intermediary device, use devices and search tools on the internet to find answers, as well as adjust the camera's rotation angle to avoid remote supervision from teachers. These acts of cheating with high pervasiveness are also found in studies of online testing or assessment during distance learning due to the impact of the Covid-19 pandemic [36,5,16]. Meanwhile, the analysis results for acts of plagiarism show that acts belonging to this group are not common in remote online exams.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…More specifically, the results on the group of cheating indicate that the most common acts are: Students look for answers in learning materials placed in locations that cameras cannot monitor; Students send test answers to each other through an intermediary device, use devices and search tools on the internet to find answers, as well as adjust the camera's rotation angle to avoid remote supervision from teachers. These acts of cheating with high pervasiveness are also found in studies of online testing or assessment during distance learning due to the impact of the Covid-19 pandemic [36,5,16]. Meanwhile, the analysis results for acts of plagiarism show that acts belonging to this group are not common in remote online exams.…”
Section: Discussionmentioning
confidence: 79%
“…Some previous studies have also demonstrated that some academic dishonesty acts in remote online exams, such as cheating, are easier to perform than in traditional offline exams [35]. However, cheating motivations in online and offline exams are not significantly different [36]. More specifically, the results on the group of cheating indicate that the most common acts are: Students look for answers in learning materials placed in locations that cameras cannot monitor; Students send test answers to each other through an intermediary device, use devices and search tools on the internet to find answers, as well as adjust the camera's rotation angle to avoid remote supervision from teachers.…”
Section: Discussionmentioning
confidence: 99%
“…These create a more stressful environment under which students must complete assessment tasks (Goonan, 2003). While anxiety often has negative consequences on exam performance (Cassady, 2004;Salend, 2011), the delivery of exams online introduces the problem of student cheating under unsupervised conditions (Turner and Uludag, 2013), which has been one of the key limitations to the use of online technologies for summative assessment. Every attempt was made to provide an experience with the TabExam that was identical to the paper exam, with the exception of its execution on digital format.…”
Section: Discussionmentioning
confidence: 99%
“…As part of digitalization, students' evaluation techniques have also been transferred from traditional pen and paper-based examinations to online platforms [35]. The detection and mitigation of online cheating may be more difficult even when the motivations for cheating in offline and online exams are not noticeably different [36]. In this way, it is easy to take the evaluation for a large number of students, do the grading which can sometimes be automated and most importantly record the evaluation information that can be accessed and updated in the simplest way.…”
Section: Evaluation Techniques For Online Examinationsmentioning
confidence: 99%